1997
DOI: 10.1161/01.cir.96.9.2987
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Prognostic Assessment of Blood Pressure Response During Exercise in Patients With Hypertrophic Cardiomyopathy

Abstract: A normal exercise blood pressure response identifies low-risk young patients with HCM. An ABPR identifies the high-risk cohort; the low positive predictive accuracy, however, indicates that further risk stratification is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
154
0
9

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(165 citation statements)
references
References 24 publications
2
154
0
9
Order By: Relevance
“…51,52 It is associated with sudden death especially in individuals under fifty years of age. 52 Evidence of this abnormality is present in roughly 30% of the patients.…”
Section: Abnormal Blood Pressure Response To Exercise While Standing mentioning
confidence: 99%
See 2 more Smart Citations
“…51,52 It is associated with sudden death especially in individuals under fifty years of age. 52 Evidence of this abnormality is present in roughly 30% of the patients.…”
Section: Abnormal Blood Pressure Response To Exercise While Standing mentioning
confidence: 99%
“…43 Among young people it presents a reduced positive predictive value and an elevated negative predictive value. 51,52 It develops by inappropriate vasodilation of the unexercised skeletal muscle vessels and is associated with the stimulation of baroreceptors due to wall stress or ischemia. 51,52 The lack of pathological vasoconstriction or dilation of the capacitance vessels contributes to the generation of blood pressure abnormalities during or immediately following upright physical exercise.…”
Section: Abnormal Blood Pressure Response To Exercise While Standing mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the traditional clinical criteria of worse prognosis [5][6][7][8][9][10][11][12] and the genetic advances with regard to the discovery of over 200 mutations that are responsible for the disease [13][14][15][16][17][18] , the stratification of sudden death risk in hypertrophic cardiomyopathy (HCM) continues to be a true challenge due to the great heterogeneity of its presentation, as most individuals remain asymptomatic during their entire lives and some others present sudden death as first symptom.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Furthermore, the literature suggests that abnormal BPR is caused by an inappropriate decrease in systemic vascular resistance (SVR), 9,10 and subendocardial ischemia. 11 On the other hand, we previously reported that some patients with nonobstructive HCM showed systolic dysfunction during exercise.…”
Section: Introductionmentioning
confidence: 99%